Amiodaron dan Toksisitas terhadap Paru - Kemalasari Nas Darisan; Jamal Zaini; Yoga Yuniadi (The Indonesian Heart Association, 2013)
Amiodarone is an antiarrhythmic agent commonly used to treat supraventricular and ventricular arrhythmias. The drug prevents the recurrence of life-threatening ventricular arrhythmias and produces a modest reduction of sudden deaths in high-risk patients. This drug is an iodine-containing compound that tends to accumulate in several organs, including the lungs. It has been associated with a variety of adverse events. Of these events, the most serious is amiodarone pulmonary toxicity. Although the incidence of this complication has decreased with the use of lower doses of amiodarone, it can occur with any dose. Because amiodarone is widely used, all clinicians should be vigilant of this possibility. Pulmonary toxicity usually manifests as an acute or subacute pneumonitis, typically with diffuse infiltrates on chest x-ray and high-resolution computed tomography. Other, more localized, forms of pulmonary toxicity may occur, including pleural disease, migratory infiltrates, and single or multiple nodules. With early detection, the prognosis is good. Most patients diagnosed promptly respond well to the withdrawal of amiodarone and the administration of corticosteroids, which are usually given for four to 12 months. It is important that physicians be familiar with amiodarone treatment guidelines and follow published recommendations for the monitoring of pulmonary as well as extrapulmonary adverse effects.